Study of methods for estimating cyber reliability of infocommunication systems - Майкл Ннамді Нвезе (My University, 2022)
The research object is the process of assessing the cyber reliability of infocommunication systems and networks. The subject of research is methods and means of assessing the cyber reliability of infocommunication systems and networks. The purpose of the work is the analysis of methods for assessing the vulnerabilities of infocommunication systems and networks and quantitative measurement of cyber resilience of modern information communication systems and networks and their elements. Research methods – empirical analysis, formalization, methods of graph theory, game theory, stochastic analysis. Currently, the task of quantitative assessment of cyber reliability of infocommunication systems and networks is an extremely important step in ensuring and improving the level of information security. This work provides a classification of attacks on infocommunication systems and networks, considers the main standards for ensuring information security and indicates their features. Approaches to vulnerability assessment and quantitative measurement of cyber resilience of the infocommunication systems and networks and their elements are considered. The calculation was carried out for a telecommunication network with a given structure.
Keywords: infocommunication system; cyber reliability; assessments; vulnerability test; cyber resilience assessment; critical nodes; critical arcs